EMOTIONAL INTELLIGENCE AND LIFE SATISFACTION AMONG STUDENTS IN KLANG VALLEY MALAYSIA - Kunnasunthary Ramachandran; Hanina H. Hamsan; Azlina Mohd Khir (INTERNATIONAL JOURNAL OF MODERN TRENDS IN SOCIAL SCIENCES (IJMTSS), 2024)
A person emotion and intelligence have a significant impact on his or her satisfaction level of life. This study explored the relationship between emotional intelligence and life satisfaction among undergraduate students. A total of 600 undergraduate students were selected as participants via random sampling at four universities in Klang Valley area, Malaysia. The Emotional Scale (SEIS) and The Extended Satisfaction with Life Scale instruments were used in this study. Data were collected via the survey questionnaire and analyzed by using Statistical Package Social Science (SPSS). The result shows a student with positive emotional intelligence, has a high level of satisfaction in campus life. Therefore, besides academic achievement, enhancing students’ capability to observe, manage and utilize positive social skills bring out a successful satisfaction of life. The finding of this study improves the understanding of emotional intelligence in indicating life satisfaction, especially in managing and utilizing emotion among students. Hereby, universities administrative might realise how important emotional intelligence level in student’s lifestyle. Therefore, this study became a basis warning model to improve student’s emotional intelligence and life satisfaction at the campus.